2022
DOI: 10.3390/molecules27103103
|View full text |Cite
|
Sign up to set email alerts
|

Mimic Pork Rinds from Plant-Based Gel: The Influence of Sweet Potato Starch and Konjac Glucomannan

Abstract: This study investigated the effect of sweet potato starch (SPS) and konjac glucomannan (KGM) on the textural, color, sensory, rheological properties, and microstructures of plant-based pork rinds. Plant-based gels were prepared using mixtures of soy protein isolate (SPI), soy oil, and NaHCO3 supplemented with different SPS and KGM concentrations. The texture profile analysis (TPA) results indicated that the hardness, cohesiveness, and chewiness of the samples improved significantly after appropriate SPS and KG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…After frying, there were still differences in the texture of the five PBPs, with hardness ranging from 3751.96 g to 9077.24 g, viscosity ranging from 3.89 g to 6.45 g, springiness ranging from 0.80% to 0.86%, and chewiness ranging from 3162.44 g to 9303.22 g. However, the hardness, viscosity, and springiness of PBP3, C-PBP1, and C-PBP1 were similar to APM. This may be related to protein deformation, polysaccharide breakdown, and disruption of the gel system [ 19 , 20 ]. Giang [ 13 , 18 ] et al found that both plant-based beef burgers and animal beef burgers had similar textural changes after being fried, while plant-based beef was softer than animal beef, which was consistent with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After frying, there were still differences in the texture of the five PBPs, with hardness ranging from 3751.96 g to 9077.24 g, viscosity ranging from 3.89 g to 6.45 g, springiness ranging from 0.80% to 0.86%, and chewiness ranging from 3162.44 g to 9303.22 g. However, the hardness, viscosity, and springiness of PBP3, C-PBP1, and C-PBP1 were similar to APM. This may be related to protein deformation, polysaccharide breakdown, and disruption of the gel system [ 19 , 20 ]. Giang [ 13 , 18 ] et al found that both plant-based beef burgers and animal beef burgers had similar textural changes after being fried, while plant-based beef was softer than animal beef, which was consistent with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
“…A loose protein spatial network structure and low ionic strength led to higher WHC [ 14 ]. Zhang et al [ 19 ] studied the preparation of plant-based pork skin and found that soy protein concentrate, soy isolate, and soy oil would line up into a three-dimensional network structure to retain water. Cornet et al [ 24 ] found that increased ionic strength resulted in lower WHC in meat substitutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that the addition of the dietary fiber increased the firmness, hardness, springiness, cohesiveness, resilience, and chewiness of the plant‐based sausages, which altered their sensory attributes. In another study, TPA was used to characterize the effects of sweet potato starch and konjac glucomannan on the textural attributes of plant‐based pork rinds formulated from emulsion gels composed of soy protein and soy oil (Zhang, Huang, et al, 2022). The hardness, cohesiveness, and chewiness of the pork rind analogs could be optimized by controlling the amounts of starch and glucomannan added.…”
Section: Modeling Of Rheological Properties Of Solid‐like Plant‐based...mentioning
confidence: 99%
“…Compared with the structure of single-tissue protein, the structure of recombinant plant-based meat alternatives is more complete and more suitable for cooking, successfully simulating the appearance, texture and flavor of animal meat products, and has, consequently, become a hot spot for development in the food industry. At present, recombinant plant-based meat alternative products include relatively simple mincemeat products, such as plant-based burger patties, plant-based sausages and plant-based meatballs, while complete meat blocks, such as pork pancetta and snowy beef, are neither widely simulated nor studied due to the complexity of their compositional structure [ 11 ]. Similar products did appear at the early stage of recombinant plant protein development, due to the demand for such meat products from vegetarian; however, these were mostly distorted and poorly simulated.…”
Section: Introductionmentioning
confidence: 99%